AB0590 Differential Platelet Count in Active versus Inactive Anca-Associated Vasculitis (AAV) and Aav-Patients with Systemic Infections. (10th June 2014) - Willeke, P.; Becker, H.; Schlüter, B.; Jacobi, A.
Abstract : Background: There is increasing evidence that platelets (PLT) are protagonists of inflammation in addition to their haemostatic role. Objectives: To analyse PLT counts in patients with ANCA-associated vasculitis (AAV) at different states (active disease, in remission and during systemic infections) and to correlate the data with clinical parameters and markers of inflammation. Methods: PLT counts of patients with newly diagnosed active AAV were analysed before initiation of therapy and in remission. Results were correlated to clinical manifestations of AAV, the Birmingham Vasculitis Activity Score (BVAS) and laboratory findings. In addition platelets were analysed during systemic infections in AAV patients. Results: We identified 81 patients with active disease before therapy was initiated and 18 patients with AAV and evidence for systemic infections (age 58.7±16.9, 25 were female). Infections were pneumonia (n=14) and febrile urinary tract infections (n=4). PLT counts were significantly higher in patients granulomatosis with polyangiitis (n=52; 414±150 PLT/nl) compared to patients with microscopic polyangiitis (n=23; 333±109 PLT/nl) or eosinophilic granulomatosis with polyangiitis (n=12; 358±141 PLT/nl); (p<0.01). PLT in all active AAV patients groups were significantly higher than in AAV-patients with systemic infection (225±77 PLT/nl; p<0.01). After receiving remission PLT decreased significantly in all AAV patients groups (231±85 PLT/nl; p<0.01). There was a strong correlation of PLT and the BVAS score (r=0.461; p<0.001) and a weaker correlation of PLT with leukocyte counts and the CRP-value during active disease. Conclusions: PLT are increased in patients with active AAV and correlate with the disease activity index. PLT counts may help to differentiate between active disease and systemic infections. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5464